Influence of Multiple Animal Scanning on Image Quality for the Sedecal SuperArgus2R Preclinical PET Scanner - Efthimiou, Nikos; Wright, John D.; Clayton, Luke; Renard, Isaline; Zagni, Federico; Caribé, Paulo R.R.V.; Archibald, Stephen J.; Cawthorne, Christopher J. (Frontiers in Physics, 2021)
Background: Increased throughput in small animal preclinical studies using positron emission tomography leads to reduced costs and improved efficiency of experimental design, however the presence of multiple off-centre subjects, as opposed to a single centred one, may affect image quality in several ways. Methods: We evaluated the count rate performance using a NEMA scatter phantom. A Monte Carlo simulation of the system was validated against this dataset and used to simulate the count rate performance for dual scatter phantoms. NEMA NU4 image quality phantoms were then scanned in the central and offset positions, as well as in the offset position next to a uniform activity phantom. Uniformity, recovery coefficients and spillover ratios were then compared, as were two time frames for acquisition. Results: Count rate performance assessed with a single NEMA scatter phantom was in line with previous literature, with simulated data in good agreement. Simulation of dual scatter phantoms showed an increase in scatter fraction. For the NEMA Image Quality phantom, uniformity and Recovery coefficients were degraded in the offset, and dual phantom cases, whilst spillover ratios were increased, notably when the chamber was placed nearest the gantry. Image quality metrics were comparable between the 20- and 10 min timeframes Conclusion: Dual animal scanning results in some loss of image quality on the Sedecal Argus PET scanner; however, this degradation is within acceptable limits.